Experimental and numerical investigation of the behavior of ship windows subjected to quasi-static pressure loads. (March 2016) - Gerlach, B.; Fricke, W.
Abstract: High load-carrying capacity of ship windows is important for ship safety. This aspect has recently become significant after several incidents with broken windows in superstructures had occurred. In order to get more insight into the failure behavior and into the interaction between glass windows and surrounding wall structure, experiments and numerical investigations of windows subjected to quasi-static as well as impact loads were performed. In this paper quasi-static ultimate load tests with full-scale test models, each containing a clamped or bonded laminated safety glass window, are described. Finite element modeling of the steel structure, laminated glass, and elastomer bonding or gasket is outlined in detail. Material data are based on small-scale tests of steel and glass specimens, and on published data. Afterwards a method to calculate failure probabilities of glass panes under pressure loads is presented. Failure probabilities for the glass panes in the tests are determined and failure mechanisms are clarified. Finally, hints for designing safe windows and for improving window designs are given. Highlights: Quasi-static ultimate load tests with ship windows accompanied by extensive numerical investigations are presented. Large laminated safety glass windows withstand high pressures because of the membrane effect. Large deflections of glass and metal structure cause early failure due to slip-out of glass panes. Non-linear finite element simulations are valuable to analyze failure mechanisms and to improve window designs. The determination of failure probabilities of glass is helpful for the assessment of measures to increase window safety.